Kwestia interpunkcji w utworach poetyckich Ignacego Krasickiego. Spostrzeżenia i uwagi w związku z edycją krytyczną wierszy - Kostkiewiczowa, Teresa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The issue of determining punctuation of former periods’ compositions in preparation for a critical edition is complicated and arises problems often difficult to solve univocally. This article treats of such situations based on Ignacy Krasicki’s poems, proposes solutions justified by the analysis of the text’s meanings and also points at situations where alternative versions are permissible. The reasoning arrives at a conclusion on editor’s work including punctuation, as endeavors of interpretative nature that are important for the understanding of a text and of its meanings.